The trigger factors of domestic violence among mothers during pregnancy - Natalia Damaiyanti Putri Raden; Lilik Zuhriyah; Sri Andarini (International Journal of Public Health Science (IJPHS), 2023)
Domestic violence also called "domestic abuse" or "intimate partner violence", can be defined as a pattern of behavior in any relationship that is used to gain or maintain power and control over an intimate partner. Abuse is physical, sexual, emotional, economic, or psychological actions or threats of actions that influence another person. This includes any behaviors that frighten, intimidate, terrorize, manipulate, hurt, humiliate, blame, injure, or wound someone. Furthermore, it is common among women, which globally increases the risk of pregnancy. This research aimed to analyze the trigger factors of domestic violence among pregnant women. The interviews with eight participants were analyzed using the Colaizzi method. It produced five main themes, namely, the husband is often angry and fight since having an affair, income is not sufficient to fulfill the monthly needs, fights because the husband feels jealous, the husband is temperament, smacks, and also berates when drunk, fights because husband spends money on gambling.